Level of Farmers Satisfaction with Agricultural Extension Services in Gapoktan Mekarjaya Pulomulya Village Lemahabang District Karawang Regency - Aisyah Maulidina; Muharam Muharam; Kuswarini Sulandjari (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2023)
Agricultural extension is a non-formal education for farmers and their families with the aim of changing knowledge, attitudes, skills, and towards a better. The level of satisfaction is a feeling experienced by someone after making a comparison between the desired level of expectation and the level of service that has been felt. The problem in Gapoctan Mekarjaya is that the counseling that has been running so far is uncertain the role of extension agent when the counseling occurs if there is a program from the government, and when the program ends, there is no follow up of extension activities to meet the needs of farmers by existing counseling that can further increase the capacity of farmers. The sample is determined in a proportional stratified random sampling by using the purposive sampling method for farmers respondents with known population sizes, they can use slovin samples taken by 40 farmer respondents. Quantitative research techniques. The data analysis used is Likert scale, category, customer satisfaction index, importance performance analysis, and descriptive. The results showed that in general, the level of importance of extension services to farmers was included in the criteria for a high average score of 143,64 and a total average of 3,88. The performance of extension services to farmers is included in the medium criteria of an average total score of 120,16 and a total average total score of 120,16 and a total average of 3,11. The farmers satisfaction level is in the satisfied category of CSI value of 77,73. Extension services in meeting the needs and needs of farmers need to be prioritized. Keywords: extension service performance, importance level, satisfaction level, priority